Peran YBM PLN UID Sumatera Utara Terhadap Pemberdayaan Ekonomi dan Kesejahteraan Masyarakat - Azura Rizti Saladin; Muhammad Yafiz (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The problem of poverty is a very complex problem in Indonesia, therefore changes need to be made from all parties, both together and in coordination. The community empowerment initiative is one of the strategies for overcoming poverty. YBM PLN UID North Sumatra is a zakat amil institution in various regions which then has a very important role in carrying out the economic empowerment process for the community so that they are able to live independently and empowered. The purpose of this research is to find out the program, program implementation and find out the results of the program as well as the role obtained by YBM PLN UID North Sumatra in empowering economic society. Then this researcher used a qualitative research method with a descriptive approach. This method is a method that aims to depict or describe actual events in the field. Data collection techniques in this research used observation, interview and documentation techniques. The results of this research show that YBM PLN plays a role as an agent of change and leader or mentor in empowering the community's economy with the programs created by YBMPLN in an effort to empower the community which are currently running well, even providing an extraordinary positive impact on the beneficiaries. From these indicators of success, it can be seen as follows, namely: increasing people's income, increasing people's abilities and potential.